Cover Picture: Dissipative Catalysis with a Molecular Machine (Angew. Chem. Int. Ed. 29/2019). Issue 29 (25th June 2019) - Biagini, Chiara; Fielden, Stephen D. P.; Leigh, David A.; Schaufelberger, Fredrik; Di Stefano, Stefano; Thomas, Dean
Abstract : Pulse quickening catalysis In their Communication on page 9876 ff., D. A. Leigh an co‐workers report the induction of an out‐of‐equilibrium state in a synthetic molecular machine in order to control catalysis. A rotaxane is transiently converted from its resting state into a catalytically active form upon consumption of a chemical fuel, thereby allowing temporal control of a coupled chemical reaction. Image: Dr. Anna Tanczos, SciComm Studios.